Mobile learning innovation to improve vocational high school students’ mathematical communication skills and dispositions - Rohmah, Luluk; Yaniawati, Poppy; Saputra, Irwan; Sharif, Sabariah (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
Students require engaging and relevant instructional materials to enhance their mathematical communication skills and mathematical dispositions. This study aims to develop mobile learning-based instructional materials on matrix topics integrate mathematical communication and disposition for vocational high school students. The research employed a Research and Development (R&D) method with a mixed-method approach, following the 4D development model: define, design, develop, and disseminate. The trials were involved 8 subject matter experts and 8 media experts, as well as 15 grade XII AP students for small-group trials and 30 grade XI AP students for large-group trials at SMK Bina Sarana Industri Subang. Data were collected through interviews, questionnaires, and tests. The results indicate that the mobile learning materials on matrix topics are of acceptable quality and received positive responses in terms of students' mathematical dispositions. However, no significant correlation was found between students’ mathematical communication skills and their mathematical dispositions. These findings suggest the need for further development in integrating mathematical communication and disposition into instructional materials.